Home-based care in post-discharge arrhythmia management: a review - Kerkar, Prafulla; Harikrishnan, S.; Sawhney, J. P. S.; Kapoor, Aditya; Gharat, Chetan (International Journal of Research in Medical Sciences, 2025)
Arrhythmia, particularly atrial fibrillation (AF), is a common heart rhythm abnormality with risk factors including age, high blood pressure, alcohol consumption, congenital heart disease, and lung disease. Proper management is critical to prevent complications, enhance quality of life, enable early detection, and reduce healthcare costs. Multidisciplinary patient care and routine follow-up are essential for improving adherence, reducing hospital readmissions, and boosting survival rates. Home-based care has proven to be as effective as clinical settings in reducing mortality and rehospitalization rates. However, challenges such as cost, accessibility, safety, cost, and regulatory issues persist. A comprehensive workbook, including care pathways, dietary guidelines, exercise recommendations, and follow-up procedures, is essential for supporting home care providers and enhancing patient outcomes. A thorough literature review was conducted across multiple databases, including PubMed, Google Scholar, Scopus, and Web of Science, to identify studies related to arrhythmia and home-based post-discharge care. Data from these studies were analyzed and summarized in this review article and highlighted the importance of incorporating home-based care into post-discharge arrhythmia management.